INVISIBLE BURNOUT: THE UNSEEN IMPACT OF ALWAYS-ON CULTURE IN KNOWLEDGE WORKERS - K. M. Faisal Reza (Adisam Publisher, 2025)
The phenomenon of an always-on culture, characterized by the expectation to be constantly connected and responsive to work, has become a hallmark of the modern workplace, particularly among knowledge workers. This culture gradually creates psychological stress that is difficult to immediately recognize but has a significant impact on mental health and productivity. This study aims to uncover and analyze the phenomenon of invisible burnout, a hidden but persistent mental exhaustion caused by the pressure of working without clear time limits. Using a literature review method, this study examines various previous studies that discuss the correlation between digital technology, continuous workloads, and their impact on worker well-being. The results show that invisible burnout often goes undetected because it is masked by a culture of high productivity and the normalization of working outside of office hours. This research highlights the importance of healthy work policy interventions and organizational awareness of work-life balance as preventative measures against the risk of long-term, invisible burnout.